Measurement of the Z / γ∗→ ττ cross section in pp collisions at √s=13TeV and validation of τ lepton analysis techniques - KAYA, MİTHAT (My University, 2018)
© 2018, CERN for the benefit of the CMS collaboration.A measurement is presented of the Z / γ∗→ ττ cross section in pp collisions at s=13TeV, using data recorded by the CMS experiment at the LHC, corresponding to an integrated luminosity of 2.3fb-1. The product of the inclusive cross section and branching fraction is measured to be σ(pp→Z/γ∗+X)B(Z/γ∗→ττ)=1848±12(stat)±67(syst \,+\,lumi) pb, in agreement with the standard model expectation, computed at next-to-next-to-leading order accuracy in perturbative quantum chromodynamics. The measurement is used to validate new analysis techniques relevant for future measurements of τ lepton production. The measurement also provides the reconstruction efficiency and energy scale for τ decays to hadrons+ντ final states, determined with respective relative uncertainties of 2.2 and 0.9%.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)